Price adjustment in world wine markets: A cointegration analysis - Juan S. Castillo Valero; Ma Carmen García-Cortijo (Wine Economics and Policy, 2015)
World wine trade has undergone an exponential dynamic in recent years because of the fall in domestic demand of the main traditional producing countries. This study aims to measure the degree of price integration in the international wine market, within a framework where review and re-adaptation of strategies and behaviors is continuous in a scenario of increasing globalization. Prices from the principal Old World exporting countries have been taken into account, and those from New World exporters. The methodology adopted is based on estimating the Error Correction Vectors, linear and with thresholds. Results obtained show that export prices of Old World countries in the EU are homogenous and seek equilibrium within the same cointegration space; and, on the other hand, that New World exporters do not share a common behavior in their exporting dynamics. France appears as the "leader" of Old World countries, although its leadership and trend is not followed or shared by the New World exporters. However, Italy and particularly Spain are the ones cointegrated, linearly and non-linearly, with markets from New World countries, USA and Argentina. Therefore, France is reference within the EU, while New World exporters countries take Italy and Spain as reference competitors.
Keywords: 330; Cointegration; Export prices; Wine